4=29+13x

Simple and best practice solution for 4=29+13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=29+13x equation:


Simplifying
4 = 29 + 13x

Solving
4 = 29 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
4 + -13x = 29 + 13x + -13x

Combine like terms: 13x + -13x = 0
4 + -13x = 29 + 0
4 + -13x = 29

Add '-4' to each side of the equation.
4 + -4 + -13x = 29 + -4

Combine like terms: 4 + -4 = 0
0 + -13x = 29 + -4
-13x = 29 + -4

Combine like terms: 29 + -4 = 25
-13x = 25

Divide each side by '-13'.
x = -1.923076923

Simplifying
x = -1.923076923

See similar equations:

| 6c=-8+2c | | -16-6-2g=-4(-g-20) | | y+3y-1=y | | -3g+4=9-8g | | 7x-x-10=-4 | | F(-4)=3x^2+5 | | 459.90=210x+119x | | 3=9+4c | | 14v+(-4v)= | | 5-2+8v=-9-4v | | y-7/16=-5/8 | | (-8x^6)^-4/3 | | 5-7w=-8w | | 459.90=210+119x | | x^2*x-20=0 | | 1-4j=-2j-7 | | (-8x^6)^-3/4 | | 4(7h+16)=-9h-2(-18h-13) | | -3d=-8d-10 | | -15x+7y+15x-13y= | | 5s+2=6s-6 | | -17g-(-4)=-30 | | C=38.89+0.25x | | -19-(-19)-18= | | 5-4(3w-3)=-6 | | 8=3u+4u | | 8=60+4x | | -7+3f=4f+3 | | y/3-2=5/6 | | 0=x^3(4-x) | | 7w-3=6w-5 | | 7s+-5=9 |

Equations solver categories